Urban Expansion Re-Visited. - Hesse, Markus (RWTH Aachen University, 2021)
This paper deals with urban expansion, that is, the growth of cities and inner-urban areas, both inside and outside of the dedicated planning perimeters. The author aim is to give a brief overview of how this subject matter can be discussed from a contemporary perspective, with a certain focus on big projects that have evolved in recent decades and are on the rise again. Towards that end, the author will situate the subject matter in historical contexts, provide some explanation as to the 1970s and more recent dynamics, and discuss how large-scale urban projects are being implemented. While big projects pursue different ambitions – such as economic, socio-demographic or ecological goals – they are set in place by a kind of managerial urbanism, often prioritise economic gains and thus challenge urban policy and planning. The paper concludes with a call to contextualise the variegated outcomes of new urban projects and to develop appropriate methods for monitoring and assessing urban life in these quarters.
Keywords: Stadtwachstum; Stadtgebiet; Reurbanisierung; Nachkriegsentwicklung; Historische Entwicklung; Stadtpolitik; Stadtplanung; Großprojekt